Poverty and Tourism: Strategies and Opportunities in Karimunjawa Island, Central Java - Setiawan, Budi; Rijanta, R; Baiquni, Muhammad (Journal of Indonesian Tourism and Development Studies, 2017)
This article analyzes the strategies of Pro-Poor Tourism (PPT), i.e. the strategies to increase the benefits for poor people from tourism development. It explained the view that tourism, on a small or large scale, has a positive contribution to increased sources of income, creation of employment opportunities, and community development. However, there are still problems in developing the potentialities of the local labor force to contribute in the tourism sector. The development of tourism in Karimunjawa over the past ten years has undergone good progress, but the poverty rate in Karimunjawa is still fairly high. The problem of poverty is a complex one and is linked to a decrease in the main sources of earnings, i.e. fisheries and agriculture. The underlying concern is the fact that the growth of tourism in Karimunjawa has fostered the growth of resorts, hotels or the service sector owned and run by big investors, vis-à-vis the scant participation of the poor. The dominant types of job that the local community does are as employees or hired workers, and they are rarely involved directly in the planning and development of tourism, thereby restricting the potential role of the poor in the tourism sector in Karimunjawa. This study recommends strategies for the empowerment of the local community to enable them to make a considerable contribution to tourism in Karimunjawa in an endeavor to alleviate poverty and enhance the quality of human resources. One strategy recommended in this article is the adoption of a pro-poor policy through vocational training in tourism for the local community of Karimunjawa. Keywords: Karimunjawa, poverty, Pro-Poor Tourism, tourism, vocational training.